IMPACT OF SOCIAL ADVERTIZING ON FORMING CIVIL COMPETENCES OF PUBLIC SERVANTS AND LOCAL GOVERNMENT OFFICIALS - Hryshyna N.M.; Revenko T.V. (Pressing Problems of Public Administration, 2017)
The paper explores the essence of a competence-based model of training public servants and localgovernment officials, investigates the special features of civil competences and the impact of socialadvertizing on their formation and development.